Color preferences for knitted top wear of U.P female college students - Sangel, Maria Ashara Nanquil; Escano, Maria Monica R. (2002.)
This study is an analysis of the color preferences for knitted top wear of female college students of the University of the Philippines. The subjects of the study were composed of 100 randomly selected students residing in the following dormitories: Kamia Residence Hall, Ilang-Ilang Residence Hall, and Sampaguita Residence Hall. A questionnaire was used for the purpose of classifying the respondents according to their skin tone type (Fair, Medium, Dark) and body proportion type (Tall and Slender,Tall and Chubby, Petite and Slender, Petite and Chubby, and Average); identifying which colors the respondents like the most, wear most often, and find most difficult to wear; and knowing the reasons for these color choices. In the interpretation of data, the color choices of the respondents were cross-tabulated according to the skin tone and body proportion types of the respondents. Likewise, the reasons given by the respondents for their color choices were also cross-tabulated according to the skin tone and body proportion types of the respondents. Subsequently, a comparison was made to identify any similarities and/or differences between the color preferences of the respondents. Findings showed that the most-liked colors were Black, White, Sky Blue, and colors with light values in the shades of blue and violet. Respondents based their color preferences on their favorite colors and those that reflected their personalities most. From the comparison made on the color preferences of the respondents according to their body proportion classifications, it was concluded that the type of body proportion had an effect on the colors the respondents like most. This conclusion was based on the observation that respondents with chubby body proportions (Tall and Chubby, Petite and Chubby) chose dark colors more frequently than those who have slender body proportions (Tall and Slender, Petite and Slender). On the other hand, it was concluded that the color preferences of respondents were also based on their skin tone type. This conclusion was based on the observation that respondents with fair skin tone chose the most number of bright colors, although most respondents chose different colors with different values and intensities. It was also observed that colors most difficult to wear were those which have great intensities. The most frequent reasons given by the respondents were that the colors were too bright, too loud and flashy, and not visually pleasing. Analysis on the data gathered showed the same pattern for all skin tone and body proportion types of respondents. Thus, it was concluded that the selection of colors most difficult to wear was not based on the type of skin tone and body proportion of the respondent. The analysis of data also confirmed that Black and White were the most frequently worn colors. Other colors in the shades of blue, violet, red, and gray were also chosen, yet among these colors Sky Blue remained the third most often worn color. Most of the colors chosen by the respondents have light values. However, respondents with fair skin tone more frequently chose dark colors. Meanwhile respondents with medium and dark skin tone more frequently chose dark colors. Meanwhile respondents with chubby body proportions chose colors with dark values more often that those with slender body proportion. Therefore, it was concluded that the type of body proportion of the respondents have affects in their choices on the colors they most often wear. However, since only slight differences were observed on the color preferences of the respondents according to their skin tone types, it was concluded that skin tone type hardly affects the respondents' choice for the colors they wore often.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Color--Psychological aspects; Women college students--Philippines--University of the Philippines--Clothing.